Rancang Bangun Aplikasi Pengoptimalan Komposisi Pakan Kambing Peranakan Etawa Menggunakan Metode Pearson Square Pada Peternakan Nyoto - Sutrisno, Alfian; Wibowo, Januar; Setyawan, Henry Bambang (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Abstract: Goat fattening business in Indonesia generally still used traditional system. In fact, managed properly can bring higher profit. Difficulties in management of fattening goats resulted in difficulty finding replacement feed that delivers optimum results in the maintenance and the purpose of fattening goats, because it requires a long time to find out the results to added weight. Based on the issue above, the optimizer application architecture feed the goats can be formulate that is capable of sufficient nutritional needs of goats such as proteins and nutrients that are appropriate to the needs of each goat.